The Impact of Housing on Primary Student’s Welfare and Role of International Organizations to improve it - Bahare Fallahi, Mohtaram Rabbani Masoumeh Pourrajab (Journal of Educational, Health and Community Psychology, 2014)
Abstract The purpose of this literature review paper is to determine the role of housing availability in improving well-being in children’s life and prevention of child abuse by considering the role of international organizations. This review shows that having a suitable home has an important role in succeeding the academic achievement among students, and also, homeless children more than others suffer from lack of health, physical problems and child abuse. Furthermore, this study finds that homeless school students more than their peers have a problem about academic achievement. This paper also supports the need of improving legal ways to respond to the problem of homeless among students. Key word:  Housing, Student’s welfare, International organization, Child abuse, Academic achievement